Kino zapracowane - Rojek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
The Overworked Cinema In her polemical article, the author argues with the thesis of Jakub Majmurek, who expects Polish cinema to tackle with the image of the Catholic church. It is being proven that such doctrinal disputes should never be the main purpose of filmmaking. The cinema, as free art, cannot be narrowed to ideological battlefield.